Pengaruh Disiplin Kerja, Motivasi dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kota Balikpapan - Safira Salsabila Azizah; Misna Ariani; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study was to determine the influence of Work Discipline, Motivation, and Organizational Culture on Job Satisfaction of Employees at the Balikpapan City Regional Drinking Water Company (PDAM). This type of research used quantitative research. The sampling technique in this study used puposive sampling with a sample size of 75 employees at the Balikpapan City Regional Drinking Water Company. The data collection method was carried out by distributing questionnaires. This study used Smart-PLS to process the data. The data analysis method in this study used outer models, inner models, basic equations, and bootstrapping tests. The results showed that the variables of Work Discipline and Motivation influenced Job Satisfaction of Employees at the Balikpapan City Regional Drinking Water Company (PDAM), and the study showed that the variable of Organizational Culture did not influence Job Satisfaction of Employees at the Balikpapan City Regional Drinking Water Company (PDAM).